Novel agents positively impact chemotherapy and transplantation in Hodgkin lymphoma. Issue 4 (3rd April 2019) - Dahi, Parastoo B.; Moskowitz, Craig H.; Giralt, Sergio A.; Lazarus, Hillard M.
ABSTRACT: Introduction : Majority of patients with Hodgkin lymphoma (HL) can be successfully cured with frontline conventional therapeutics. Approximately 50–60% of those whose disease recur or is refractory to conventional treatment, can be cured with salvage therapies followed by autologous hematopoietic cell transplantation (AHCT). Conventional treatments, however, may cause significant long-term toxicities. Areas covered : This article reviews the treatment advances in HL with the incorporation of novel and targeted agents that are aimed to improve cure rates while reducing toxicities. Expert opinion : Brentuximab vedotin (BV) and checkpoint inhibitors have demonstrated clear clinical benefit in HL. Majority of patients receive BV before or directly after AHCT as part of salvage or maintenance regimens. In patients who relapse after AHCT, checkpoint inhibitors are the treatment of choice, either as a stand-alone therapy or more commonly as a bridge to a potentially curative allogeneic hematopoietic cell transplantation (alloHCT). A multitude of other targeted agents and combinations, as well as cellular and immunotherapeutic in HL, are under investigation.